PERAN MATEMATIKA UNTUK PERKEMBANGAN ILMU KOMPUTER PADA SMA PGRI 22 SERPONG TANGERANG SELATAN: PERAN MATEMATIKA UNTUK PERKEMBANGAN ILMU KOMPUTER PADA SMA PGRI 22 SERPONG TANGERANG SELATAN - Alaydrus, Syarifah Farrah Rizka Putri (JARI : Jurnal Pengabdian Kepada Masyarakat Republik Indonesia, 2025)
Informatics mathematics, previously known as discrete mathematics, is a branch of mathematics that studies objects that are discrete or discontinuous. Mathematics is a subject that is considered difficult for high school students to understand. So, this material is needed to increase the knowledge of SMA PGRI 22 Serpong students. This material is needed because digital computers operate discretely with the smallest units called bits or binary digits. Thus, both the circuit structure and also the execution operations of computer algorithms can be explained using discrete mathematical concepts. Mathematics learning is an activity in understanding the meaning, relationships and symbols which are then implemented in real situations. Learning mathematics is related to how it is implemented to make decisions in resolving or solving problems. The aim of this community service activity is to develop a mathematics learning model in the field of informatics, especially for SMA PGRI 22 Serpong students. This activity will produce output in the form of a journal for learning mathematics and informatics. Apart from the output target in the form of a scientific journal, we hope that this activity will have a positive impact on the audience, such as: It will be easier for students to learn, because most students prefer direct practice to theory. The direct practice in question is with examples of real cases that occur in the field of computer science.